2012
DOI: 10.1103/physrevb.86.054519
|View full text |Cite
|
Sign up to set email alerts
|

Spin-precession-assisted supercurrent in a superconducting quantum point contact coupled to a single-molecule magnet

Abstract: The supercurrent through a quantum point contact coupled to a nanomagnet strongly depends on the dynamics of the nanomagnet's spin. We employ a fully microscopic model to calculate the transport properties of a junction coupled to a spin whose dynamics is modeled as Larmor precession brought about by an external magnetic field and find that the dynamics affects the charge and spin currents by inducing transitions between the continuum states outside the superconducting gap region and the Andreev levels. This r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 71 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…In order to understand the supercurrent in ballistic Josephson junctions it is important to analyze the spectral properties of these weak links [22,23]. In a short ballistic superconductor-normal metal-superconductor (S/N/S) junction with equal gaps and at low temperatures, tunneling through Andreev bound states (ABSs) is the dominant contribution to the Josephson current [24].…”
mentioning
confidence: 99%
“…In order to understand the supercurrent in ballistic Josephson junctions it is important to analyze the spectral properties of these weak links [22,23]. In a short ballistic superconductor-normal metal-superconductor (S/N/S) junction with equal gaps and at low temperatures, tunneling through Andreev bound states (ABSs) is the dominant contribution to the Josephson current [24].…”
mentioning
confidence: 99%
“…In Refs. [29,30] it has been shown that when the nanomagnet undergoes a precession due to an external magnetic filed the Andreev levels are affected by the dynamics of the nanomagnet's spin. The resultant Andreev levels depend on the tilt angle and precession frequency.…”
Section: Resultsmentioning
confidence: 99%
“…An analytical expression for the energy of Andreev levels in this junction has been provided in Ref. [30], except a term giving rise to the Zeemann splitting which has not been given an explicit expression for it. To give an illustration for the above discussions let us calculate the energy of Andreev levels by neglecting the tilt angle dependence of this term and replacing it by an effective Zeemann splitting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations